TEKNIK ATURAN ASOSIASI UNTUK IDENTIFIKASI ANOMALI NILAI UJIAN AKHIR MAHASISWA PJJ - Arief Andriono (Universitas Muhammadiyah Semarang, 2018)
University is a distance education provider college's that uses Personal Assignment Scores, Team Assignment Scores, Quiz Score and Final Exam Score as parameters of Student Academic Performance. Anomalous data is data that deviates from a pattern in a data set. The existence of anomalous data can indicate a disturbance in a system. This study was conducted to find the association rules of academic performance parameters of student M who was studying at U University and then to identify anomaly based on the Association Rules obtained. From the research result, it is found that there is anomaly data on academic performance of student M.Keywords: association rules, anomalies, academic performance